Research on staphylococcus spp in biofilm formations in water pipes and sinsibility to antibiotics - Lancellotti, Marcelo; Oliveira, Mônica Pereira de; Ávila, Fernando Antonio de (My University, 2007)
Water from dental equipment presents risks for surgeon-dentists as well as for patients because it might work as a means of dissemination/ transmission of microoganisms. The objective of this study was to verify the quality of the water used in dental equipment by means of microbiological analysis, accomplishing the count of Staphylococcus spp.There have been collected, 160 samples of water from reserviors, taps used for hand washing, air-water syringes, and high-speed handpieces, in 40 dental offices in the city of Barretos, São Paulo. The rules concerning bacteriotogicaI analysis in cfu/mL from Standard Methods for the Examination of Water and Wastewater have been followed. The analysis of the results has made it possible to verify that out of the total of samples, 28% did not meet the standards of potability established by the American Dental Association: Regarding the origin of analyzed S. aureus., the most contaminated sites were high-speed handpicces in private offices (761%) and in, ental care plan offices (71%), followed by air-water syringe in dental care plan offices (64%). For S. epidermitis samples, the most contaminated sites were high-speed handpieces in SUS (Brazilian Government Health System) dental offices (22%) and in dental care plan offices (14%) The most contaminated sites were dental offices that saw Patients under dental care plans, Concerning tested antibiotics, the ones that presented better results as to sensibility to strain S. epidermidis were vancomycin and ciprofloxacin (100%) and, as to sensibility to strain S. aureus, it was ciprofloxacin (97%).
Keywords: Biofilm; Cross contamination; Dental office; Staphytococcus spp; Water line